THE EFFECT OF THE PULSE CURRENT IN WIRE ELECTRIC DISCHARGE MACHINE ON MEASUREMENT ERROR TOWARD ALUMINUM ALLOY: AN EXPERIMENTAL STUDY - Amrullah Amrullah; Rahman Hakim (Politeknik Negeri Batam, 2020)
This research investigates the measurement error on Wire EDM cutting products to find the pulse current's problem-solving. One of the machining parameters that affect the precision of Wire EDM is the magnitude of the current. The experimental study carried out by using the pulse current started from 4-Ampere up to 8-Ampere as the research parameters. A chamfer dimension on 6061 Aluminum alloy was investigated with the gd&t method with ISO 5459 and ISO 1101 standard. Statistic method applied and processed on Minitab with Shapiro-Wilk parameter for normal distribution. These experimental studies have a normal distribution that finds the phenomena of 8-Ampere of pulse current generate a large measurement error. Furthermore, in these experimental studies, the usage of a Profile Projector generates a massive measurement error, up to 64.5% compared with CMM. A strong commitment to calibrate the Profile Projector up to date to maintain the machining quality.